Regional Development in the Age of Big Data - Jankó, József; Szabó, György (Acta Geographica Debrecina Landscape & Environment series, 2018)
Our paper presents a forward looking analytical approach to the territorial development in a region of the Transylvanian Plain situated in the vicinity of Cluj-Napoca, Romania. We outlined the development of this region with the means of landscape architecture supported by a comparable assessment. In the age of Big Data we settled at creative usage of traditional analysis. We extracted yet undetected information from a limited amount of available as yet loosely related data. The key feature of the employed model is the ontological traceability of cause and effect. Although technology is available to collect enormous data, expert knowledge gained by education and professional practice cannot be overlooked. We demonstrate that this method of location based analysis is capable of delivering value added to established principles of spatial planning in the age of trustworthy, large volume, heterogeneous data.